2016
DOI: 10.1038/srep18812
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-wide study of blood pressure in African Americans accounting for gene-smoking interaction

Abstract: Cigarette smoking has been shown to be a health hazard. In addition to being considered a negative lifestyle behavior, studies have shown that cigarette smoking has been linked to genetic underpinnings of hypertension. Because African Americans have the highest incidence and prevalence of hypertension, we examined the joint effect of genetics and cigarette smoking on health among this understudied population. The sample included African Americans from the genome wide association studies of HyperGEN (N = 1083, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 59 publications
(81 reference statements)
4
23
0
Order By: Relevance
“…We replicated previously described gene-environment association loci for smoking interactions with body composition (BMI and waist circumference) (Justice et al, 2017), smoking or alcohol interaction with blood pressure (Taylor et al, 2016;Feitosa et al, 2018;Sung et al, 2018), coronary artery calcified plaque in type 2 diabetes (Divers et al, 2017) and peripheral arterial disease interaction with air pollution (Ward-Caviness et al, 2017) ( Supplementary Table 5). No SNPs from these studies showed evidence of transference of the lead SNPs to African populations in our study, but none was specifically for cIMT as the main outcome.…”
Section: Gwas Catalog Lookup For Gene-environment Interactionsupporting
confidence: 81%
See 1 more Smart Citation
“…We replicated previously described gene-environment association loci for smoking interactions with body composition (BMI and waist circumference) (Justice et al, 2017), smoking or alcohol interaction with blood pressure (Taylor et al, 2016;Feitosa et al, 2018;Sung et al, 2018), coronary artery calcified plaque in type 2 diabetes (Divers et al, 2017) and peripheral arterial disease interaction with air pollution (Ward-Caviness et al, 2017) ( Supplementary Table 5). No SNPs from these studies showed evidence of transference of the lead SNPs to African populations in our study, but none was specifically for cIMT as the main outcome.…”
Section: Gwas Catalog Lookup For Gene-environment Interactionsupporting
confidence: 81%
“…The loci included a gene-alcohol interaction on blood pressure (Feitosa et al, 2018), gene-smoking interaction on waist circumference (Justice et al, 2017), gene-smoking interaction on lung cancer (Park et al, 2015) and gene-smoking interaction on blood pressure . In Navrongo, 13 SNPs replicated previous loci for gene-smoking interaction on BMI (Justice et al, (Taylor et al, 2016). Seventeen SNPs in the combined sample replicated previously reported interaction loci for gene-diabetes interaction for atherosclerotic plaque (Divers et al, 2017), gene-alcohol interaction for blood pressure (Feitosa et al, 2018), genesmoking interaction for BMI (Justice et al, 2017) and genesmoking interaction for blood pressure (Taylor et al, 2016;Sung et al, 2018).…”
Section: Gwas Catalog Lookup For Gene-environment Interactionsupporting
confidence: 69%
“…Previous studies consistently reported that some factors had no main effects whereas the interactions played key roles. According to the evidence presented by Taylor et al, two SNPs were detected providing support for powerful genetic interactions with cigarette smoking associated with SBP in African Americans from genome-wide studies, but no main genetic effect linked to SBP was detected with only these two SNPs in the model [30]. Smoking is a major environmental risk factor of EH, and previous studies reported that interactions between environmental factors and epigenetic phenomena may be synergistic [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, three well‐established consortia (CHARGE, GBPgen, and ICBP) demonstrated that SNPs in EHBP1L1 , CASZ1 , and GOSR2 exhibit nominal evidence of age‐dependent effects on blood pressure (Simino et al, ). Sung, de Las Fuentes, Schwander, Simino, and Rao () identified several novel blood pressure loci by exploiting gene–smoking interactions from the Framingham Heart Study, Basson et al () reported an association between two novel loci (near SASH1 and KLHL6/KLHL24 ) and systolic blood pressure (SBP) modulated by tobacco smoking, and Taylor et al () identified two novel loci of NEDD8 and TTYH2 in African Americans using the gene–smoking interaction. Although these studies successfully discovered novel genetic variants through determining gene–environment interactions, there has been no attempt to identify environmental factors that interact with the GRS of blood pressure traits.…”
Section: Introductionmentioning
confidence: 99%